Kamal Sundari: A High Yielding Orange-Fleshed Sweet Potato for Konkan Region of Maharashtra - Mhaskar, N. V; Jadye, A. T; Haldankar, P. M.; Bhangare, B. N.; Mahadkar, U. V. (JOURNAL OF ROOT CROPS, 2014)
Among the tropical tuber crops, sweet potato ( Ipomoea batatas L. Lam) produces more edible energy even on marginal lands than any other major food crop. It plays an important role in the economy of poor households. Some cultivars having orange-fleshed tubers are rich source of carotene, which is a precursor of vitamin A. In order to identify a suitable cultivar of orange-fleshed sweet potato for Konkan region, an experiment was conducted during kharif (rainy) season for four consecutive years (2008 . 2011) at Central Experiment Station, Wakawali. The experiment was laid out in randomized block design with four replications. The pooled results of four consecutive years revealed that among the five entries of sweet potato, Kamal Sundari produced significantly highest tuber yield (15.67 t ha -1). Kamal Sundari also produced the highest marketable tuber yield of 11.93 t ha-1, which was significantly superior over the rest. The average marketable weight of tuber was 155 g The net returns and B:C ratio was found to be the highest in the case of the Kamal Sundari (77, 238 ha-1 and 1.47, respectively). Multi-locational trials conducted at five locations also indicated the superiority of KamalSundari (12.53 t ha-1).